PENCEMARAN YANG DISEBABKAN OLEH TUMPAHAN MINYAK DARI KAPAL MV. WAKASHIO DI PERAIRAN MAURITIUS DITINJAU DARI HUKUM LINGKUNGAN INTERNASIONAL: Pollution Caused by Oil Spill From MV. Wakashio in Mauritius Waters Viewed From International Environmental Law - Erprido Goklas; Amalia Zuhra (AMICUS CURIAE, 2025)
It is the responsibility of the government of a country to take all necessary steps to make sure that activities that are done within its jurisdiction do not cause pollution to other countries.  The role of the MV Wakashio ship as the cause of water pollution in Mauritius. In this research, one legal identification  problem is how the Japanese government is responsible for the transboundary pollution caused by the oil spill from the Bulk Carrier in the waters of Mauritius. This legal research is normative legal research that emphasizes data and information from literature. This study found that the pollution in the waters caused by a leaking bulk carrier that spilled oil in the sea off Mauritius should be held accountable by the Japanese shipping company. Japan has provided appropriate compensation to address marine pollution in accordance with Mauritius's request. This case will be reviewed under the rules of UNCLOS 1982, LLMC 1986, CLC 1992, and the 2001 Bunker Convention.